2008
DOI: 10.1007/s10704-008-9234-2
|View full text |Cite
|
Sign up to set email alerts
|

Failure initiation at a blunt V-notch tip under mixed mode loading

Abstract: A criterion to predict crack onset at a sharp V-notch tip in homogeneous brittle materials under a mixed-mode loading was presented and validated by experimental observations in a previous paper by the authors. This criterion slightly underestimates the experimental loads causing failure which is attributed to a small notch tip radius that blunts the sharp corner. This discrepancy is rigorously analyzed mathematically in this paper by means of matched asymptotics involving 2 small parameters: a micro-crack inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Several failure criteria have been proposed for V-notches (Seweryn and Mróz 1995;Seweryn and Lucaszewicz 2002;Yosibash et al 2006;Priel et al 2007Priel et al , 2008Chen and Ozaki 2008;Ayatollahi and Aliha 2009) and for U-notches (Papadopoulos and Paniridis 1988;Gómez et al 2007Gómez et al , 2008Gómez et al , 2009, providing more or less accurate predictions for the scarce experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Several failure criteria have been proposed for V-notches (Seweryn and Mróz 1995;Seweryn and Lucaszewicz 2002;Yosibash et al 2006;Priel et al 2007Priel et al , 2008Chen and Ozaki 2008;Ayatollahi and Aliha 2009) and for U-notches (Papadopoulos and Paniridis 1988;Gómez et al 2007Gómez et al , 2008Gómez et al , 2009, providing more or less accurate predictions for the scarce experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Extensions of the proposed approach to include the effect of elastic anisotropy Dunn, 1998, 1999;Paggi and Carpinteri, 2008) and the presence of a notch tip radius (Berto et al, 2009;Dini and Hills, 2004a,b;Picard et al, 2006;Priel et al, 2008) will constitute the object of further investigations. The stress characterisation performed by the authors can also aid the development of predictive tools to assess fatigue strength and fracture toughness of components in the presence of notches and complete contacts (see e.g.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that by assuming a sharp V-notch tip some failure criteria predict reasonably well both the crack initiation angle and failure load. Then, Priel et al (2008) found the criterion for sharp V-notch slightly underestimates the experimental loads causing failure which is attributed to a small notch tip radius that blunts the sharp corner. Thus, they discussed the failure initiation at a blunt V-notch tip under mixed loading.…”
Section: Introductionmentioning
confidence: 97%